Protective clothing for pesticide operators: part I – selection of a reference test chemical for penetration testing. Issue 1 (2nd January 2016) - Shaw, Anugrah; Schiffelbein, Paul
Abstract : A systematic approach was taken to develop a database for protective clothing for pesticide operators; results are reported as a two-part series. Part I describes the research studies that led to identification of a pesticide formulation that could serve as a reference test chemical for further testing. Measurement of pesticide penetration was conducted using different types of pesticide formulations. Six fabrics were tested using 10 formulations at different concentrations. Three formulations were subsequently selected for further testing. Analysis of the data indicated that, when compared with other formulations, mean percent penetration of 5% Prowl 3.3 EC [emulsifiable concentrate diluted to 5% active ingredient (pendimethalin)] is either similar to or higher than most test chemicals. Those results led to choosing 5% Prowl 3.3 EC as a reference test liquid. Part II of the study, published as a separate paper, includes data on a wide range of textile materials.